HUBUNGAN PENGALAMAN LAPANGAN INDUSTRI DENGAN MINAT BERWIRAUSAHA MAHASISWA PROGRAM STUDI PENDIDIKAN TATA RIAS DAN KECANTIKAN UNIVERSITAS NEGERI PADANG - Soviana, Eliadi - (RC-INSTITUT, 2019)
The cosmetology and beauty education study program of Padang State University is one of the majors that has courses in entrepreneurship and makeup business management, which is one of the courses as a condition for being able to carry out PLI. This study aims to a) determine the level of achievement of respondents in industry field experience, b) the level of attainment of respondents in entrepreneurial interest, c) the relationship of industry field experience to entrepreneurial interest.This type of research is quantitative descriptive with a correlational approach. This research was conducted at the students of cosmetology and beauty majoring in Padang State University, this research was conducted in September 2019 until completion. The population of this study was the cosmetology and beauty majoring students of 2015 and 2014 Padang State University as many as 50 students. The data collection technique is using a questionnaire adjusted in the form of a Likert scale that has been tested for validity and reliability. Data analysis techniques using Product Moment correlation test.Based on the research results it is known that the industry experience variable with a TCR value of 87.90% is a very high category, the variable of entrepreneurial interest with a TCR value of 83.18% is a very high category and the Pearson correlation score is 0.463. This shows that there is a moderate relationship between the two variables. While the direction that occurs is positive and a sig value of 0.001 <0.05, it can be said that the Ha hypothesis is accepted. It is expected that students from the results of this study can be used as information material for self-assessment of entrepreneurial interest after undertaking industrial field experience.